Leadership and management skills for long-term care - Sullivan-Marx, Eileen; Gray-Miceli, Deanna (Springer Pub., 2008)
While the scope of long-term care settings has expanded from nursing homes and home care agencies to assisted living facilities and community-based health services, the training for nurses, managers and administrators, medical directors, and other professionals who work in these facilities is often fragmented. This book was developed to fill a widely-recognized gap in the management and leadership skills of RNs needed to improve the quality of long-term care. The book is based around learning modules in leadership and management competencies that were site-tested in three types of long-term ca.